Assessment of quality of life among antenatal women with gestational diabetes mellitus - Malik, Renu; Roy, Susha Mary (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Pregnancy is challenging for every woman and if it is complicated with conditions like gestational diabetes mellitus (GDM), it may reduce her quality of life (QoL) significantly which increases the potential risks related to the physical and psychological health aspects related to the mother as well as for the baby thus causing a negative impact on her overall health and wellbeing. Hence, it should be given more importance by healthcare professionals. Methods: The study design adopted to assess the QoL of antenatal women with GDM was a cross-sectional research design.110 antenatal women with GDM attending antenatal OPD at selected hospitals in Bengaluru were chosen using a Non-probability convenient sampling technique. A standardized GDM questionnaire (GDMQ-36) was used to assess QoL and the data analysis was done using descriptive and inferential statistics techniques. The study was conducted from July 2022 to August 2023. Results: The study results were as follows, 74.5% of antenatal women with GDM had a moderate level of QoL, 25.5% had a high level of QoL and no antenatal women was found to have low level of QoL. 60% of antenatal women had high level of QoL in support domain and 25.5% of the antenatal women had low level of QoL in complications of GDM domains. A significant association was found between QoL and selected socio-demographic variables. Conclusions: The present Study concluded that the majority of the antenatal women (74.5%), had moderate levels of QoL and a significant association was found between QoL and socio-demographic variables.